Electrophysiology-based screening identifies neuronal HtrA serine peptidase 2 (HTRA2) as a synaptic plasticity regulator participating in tauopathy - Naizhen Zheng; Kun Li; Jing Cao; Zijie Wang; Liang Zhang; Zihao Zhao; Jiawei He; Yong Wang; Xiang Zhu; Yiqing Chen; Jian Meng; Dongdong Zhao; et al. (Translational Psychiatry)
Abstract Long-term potentiation (LTP) and long-term depression (LTD) are widely used to study synaptic plasticity. However, whether proteins regulating LTP and LTD are altered in cognitive disorders and contribute to disease onset remains to be determined. Herein, we induced LTP and LTD in the hippocampal CA3-CA1 Schaffer collateral pathway, respectively, and then performed proteomic analysis of the CA1 region. We identified 20 differentially expressed proteins (DEPs) shared by the LTP and the LTD processes. Among them, we found that HtrA serine peptidase 2 (HTRA2) was mainly expressed in neurons and that HTRA2 levels were increased in both the LTP and the LTD processes in C57BL/6 mice. HTRA2 downregulation impaired synapses and reduced ATP production in cultured primary neurons. Furthermore, adeno-associated virus (AAV)-mediated HTRA2 downregulation in the hippocampus impaired synaptic plasticity and cognitive function in C57BL/6 mice. Moreover, we found that HTRA2 expression decreased in the brains of Alzheimer’s disease patients, frontotemporal lobar degeneration with ubiquitin inclusions patients, and tauopathy model mice. Finally, we showed that lentivirus-mediated HTRA2 overexpression in the hippocampus rescued PP2B reduction, alleviated tau hyperphosphorylation, and partially attenuated synaptic plasticity and cognitive deficits in the PS19 tauopathy model mice. Our study not only indicates that HTRA2 in neurons plays an important role in regulating synaptic plasticity under both physiological and pathological conditions, but also provides a novel, electrophysiology-based strategy to identify proteins regulating synaptic plasticity systematically.